Osteonecrosis of the Knee After Anterior Cruciate Ligament Reconstruction: A Report of 5 Cases. Issue 3 (24th March 2015) - Lansdown, Drew A.; Shaw, Jeremy; Allen, Christina R.; Ma, C. Benjamin
Background: Anterior cruciate ligament (ACL) reconstruction is performed commonly, with a low risk of complication. Osteonecrosis of the knee is a potentially devastating condition and has been observed both spontaneously and after meniscectomy, although osteonecrosis has not been described as a complication after ACL reconstruction. Purpose: To describe the development of osteonecrosis of the knee in 5 patients after arthroscopic ACL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: This study involved 5 patients (mean age, 33.2 years) who developed osteonecrosis of the knee after ACL reconstruction. A retrospective chart review was performed to identify clinical characteristics and surgical factors present in each of the 5 cases. Results: In 4 cases, the pathologic changes were present in both the medial and lateral femoral condyles, with isolated lateral condyle changes in the other case. The mean time to diagnosis was 11.6 months. These patients underwent an average of 1.8 additional surgical procedures after the diagnosis of osteonecrosis. Conclusion: Osteonecrosis of the knee is a rare outcome after ACL reconstruction. We are unable to identify clear risk factors for the development of this complication, although we hope the presentation of these cases will help promote the identification of other cases in future studies.